Assessing the potential of the unexploited Atlantic purple sea urchin, Arbacia punctulata, for the edible market - Suckling, Coleen C.; Zavell, Max D.; Byczynski, Anna L.; Takeda, Brian T. (Frontiers in Marine Science, 2022)
The global demand for sea urchin as seafood is currently unmet. Despite exploitation of > 40 species across the world, there is a need to identify other candidate species, especially in regions where diversification in production is sought where species are considered native. The Eastern US presents an opportunity to determine the marketability of the currently unexploited Arbacia punctulata which is naturally distributed from Massachusetts and southwards into the Gulf of Mexico. To determine whether A. punctulata had market potential, it was fed one of the following diets to determine whether the gonad tissue (uni) could be manipulated to increase gonad mass and improve gonad color for the market: dried Ulva lactuca, Salmon pellets (Skretting), Tilapia pellets (Ziegler) or an Urchinomics diet designed for sea urchins either fed for 8 weeks or 12 weeks. All of the pelleted feeds (Salmon, Tilapia and Urchinomics) increased gonad mass and altered the color. The colors of the uni were generally darker than the colors that the market would typically prefer but some individuals did exhibit colors which have been classed as acceptable to the European market. This work highlights that further research is worthwhile to assess the market potential of A. punctulata.